Il lavoro della talpa scritti su Marx - Irene Viparelli (Fuori Collana, 2018)
Conceived as a slow and inexorable path of criticism of the ideology of the bourgeois world, this collection is divided into three sections. The first: Mystification: politics and religion is dedicated to philosophy. It is in the philosophy of his time that Marx found the theoretical tools to develop his critique of the bourgeois, materialistic, dialectical and therefore revolutionary society. In the second section Crisis: reforms and conflicts, Marx's theory becomes a method of analysis of the present, a powerful epistemological apparatus that makes it possible to shed light on the intrinsically contradictory character of contemporary capitalist societies. Finally, the last section: Globalisation: resistance and fights reconstructs Di Marco's approach to the "political" question. Here his interpretation of Marx's work is filtered through the relationship with the tradition of Italian operaism, to which the author recognizes the merit of having placed the accent on revolutionary subjectivity, finding however problematic his progressive estrangement from the dialectical core of Marxism. It is in the need to re-establish the center of the Marxist criticism of reality in the capital-labour conflict that can be identified the thread of the Marxist commitment of Giuseppe Antonio Di Marco, who, convinced of the actuality and usefulness of the Marxist categories, tests them against the contradictions and conflicts of the present time.